Pharmacognostical, Phytochemical and Physicochemical Evaluation of Nardostachys jatamansi - D. Yamini; K. S. Chandrashekar; Vasudev Pai; H. N. Aswatha Ram; B. Venkatesh Kamath; Aravind Pai (Challenges and Advances in Pharmaceutical Research Vol. 3, 2022)
Nardostachys jatamansi DC is an erect perennial plant that grows to a height of 10-60 cm and has long stout woody root stock found in the Himalaya at elevations ranging from 3,500 to 5,000 metres. The current study aimed to carry out the morphological, histological, powder microscopic and phytochemical study of the rhizome of Nardostachys jatamansi. The objective of the present study is to authenticate and identify this medicinal rhizome and contribute to the prevention of its adulteration. Histological study showed presence of cork cells, medullary rays, vascular bundle, cortex and pith. Powder microscopic study showed presence of fibres, parenchyma, spiral vessel, cork cells, tracheids and starch grains. The moisture content, ash values, and extractive values of Nardostachys jatamansi were determined using physicochemical standards. Phytochemical investigation showed presence of alkaloids, carbohydrates, steroids, saponins, flavonoids, tannins, fixed oil, fats and absence of gums, mucilage, proteins and amino acids.